IMPLEMENTASI FUZZY C–MEANS CLUSTERING (FCM) PADA PEMETAAN DAERAH POTENSI TRANSMIGRASI DI JAWA TIMUR - Siti Nur Aisah; Nurcahyani, Anisa; Rini, Dian C. (Jurnal Teknik Informatika UNIKA Santo Thomas, 2022)
In an effort to achieve Indonesia's welfare, one of the Government's policies that will be implemented is the implementation and implementation of the transmigration program. In general, the transmigration program offered by the government to all people without knowing their economic and family background so that the transmigration program is not well targeted. Based on the background of the problem in this research, how to design, build, develop and implement Fuzzy C-Means Clustering on the Mapping System in East Java province for the classification of Cities/Regencies that have the potential for Transmigration. The data was obtained from data from the Central Statistics Agency (BPS) of East Java Province. The results obtained using the optimal Fuzzy C-Means method with 3 clusters.